Mobility of Non Permanent Mobility and Remmitance, Case in Tanjung Municipality, Juwiring, Klaten District - Umrotun, Umrotun (Forum Geografi, 1997)
The study Non Permanent Mobility and Remmitance was conducted in Tanjung Village Juwiring Subdistrict Klaten entral Java. Non Permanent Mobility in the village was due to the outcome of the development, particularly the transportation facilities permitting the public transport to reach the depth of the village. The mobility of going back and from village to town was the consequence of the increasing job opportunities in town and the decreasing job opportunities in the village, as well as the striking difference of wages between what the people got in the village and that in town. The mobility of the commuting people also influenced the development in the village an addition to reducing the population density in town because the people did not stay permanently. The study was that mobile agents had better income than those who were not. The study showed that the working term, the working hours per week, and the level of education did not haveÂ  significant influence on the income. This was due the fact that most of the commuting people worked in the marginal sectors. The remmitance that the people brought from town constituted the main contribution to the life of the migrants. The remmitance was mainly spent for primary needs. Based on the research outcome, it is advisable that the transportation facilities be improved so that the commutation becomes easier since non permanent mobility of is proved to have increased the quality of their life and social environment.